Correction of CFTR function in intestinal organoids to guide treatment of cystic fibrosis - Ramalho, Anabela S.; Fürstová, Eva; Vonk, Annelotte M.; Ferrante, Marc; Verfaillie, Catherine; Dupont, Lieven; Boon, Mieke; Proesmans, Marijke; Beekman, Jeffrey M.; Sarouk, Ifat; Vazquez Cordero, Carlos; Vermeulen, Francois; et al. (The European respiratory journal, 2021)
Given the vast number of cystic fibrosis transmembrane conductance regulator ( ) mutations, biomarkers predicting benefit from CFTR modulator therapies are needed for subjects with cystic fibrosis (CF). To study CFTR function in organoids of subjects with common and rare mutations and evaluate correlations between CFTR function and clinical data. Intestinal organoids were grown from rectal biopsies in a cohort of 97 subjects with CF. Residual CFTR function was measured by quantifying organoid swelling induced by forskolin and response to modulators by quantifying organoid swelling induced by CFTR correctors, potentiator and their combination. Organoid data were correlated with clinical data from the literature. Across 28 genotypes, residual CFTR function correlated (r =0.87) with sweat chloride values. When studying the same genotypes, CFTR function rescue by CFTR modulators in organoids correlated tightly with mean improvement in lung function (r =0.90) and sweat chloride (r =0.95) reported in clinical trials. We identified candidate genotypes for modulator therapy, such as E92K, Q237E, R334W and L159S. Based on organoid results, two subjects started modulator treatment: one homozygous for complex allele Q359K_T360K, and the second with mutation E60K. Both subjects had major clinical benefit. Measurements of residual CFTR function and rescue of function by CFTR modulators in intestinal organoids correlate closely with clinical data. Our results for reference genotypes concur with previous results. CFTR function measured in organoids can be used to guide precision medicine in patients with CF, positioning organoids as a potential model to bring treatment to patients carrying rare mutations.